Geotourism as a factor of development of Mid-Bosnien Schist Mountains area - Kršić, Ajdin (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
Mid-Bosnian Schist Mountains is an area of significant geological and geomorphological diversity and aim of this study is to analyse the possibility of the development of geotourism on the example of Fojnica municipality. Evaluation of natural and anthropogenic characteristics was conducted for selected old mines of the region since Fojnica has a long mining history. Results show that Bakovići mine has the greatest geotouristic potential. Further research should be directed towards the creation of a complete geotouristic product for both Fojnica municipality and the entire Mid-Bosnian Schist Mountains area.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; Fojnica; rudniki; tourism; turistična geografija; turistična ponudba; turizem